AI sebagai Alat Bantu Literasi Digital di Politeknik Pelayaran Sumatera Barat: Studi Literatur - Pratama, Yandi Nelson; Silen, Adhi Pratisha (Politeknik Pelayaran Sumatera Barat, 2025)
This literature review article aims to map out how artificial intelligence (AI) can serve as a digital literacy tool at the West Sumatra Maritime Polytechnic (Poltekpel Sumbar). Referring to the international digital literacy framework (ACRL, JISC, DigComp 2.2) and generative AI guidelines (UNESCO, 2023), the author synthesizes findings from a systematic study on AI applications in vocational higher education. The results of the study show that AI supports five main areas of digital literacy—information access, critical evaluation, creation & collaboration, security & ethics, and cadet professional identity development—through capabilities such as semantic search, writing assistants, learning analytics, and automated feedback. Emerging challenges include the skills gap between students and lecturers, data privacy, algorithmic bias, and academic integrity in maritime education. This article proposes a roadmap for AI implementation at Poltekpel Sumbar (Phases 0–3): awareness raising, pilot sandbox, integration with LMS, and ethical governance.